Upaya Peningkatan Pengetahuan Masyarakat Tentang Pengelolaan Sampah Di Pasar Inpres Ruteng Kecamatan Langke Rembong - Theofilus Acai Ndorang; Efridus man; Florentinus E. Starnal; Helena Nortiana Parung (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Pasar Inpres Ruteng is one of the shopping centers (market) in the city of Ruteng, Langke Rembong District. However, in reality up to now, it can be seen that the market conditions have not been arranged neatly and cleanly. This is indicated by various piles of garbage scattered around the market area. In the observations of the PKM team, the main cause of dirty and untidy market conditions is the lack of public awareness of market users about the importance of market cleanliness, specifically regarding the behavior of disposing of waste in its place. The purpose of PKM is to increase awareness and knowledge of market users in maintaining market cleanliness, and especially in waste management around the pasar inpres Ruteng. The methods used in PKM are counseling and socialization, as well as cleaning activities for the market environment. The community participates in finding solutions related to waste management and is involved in cleaning up the waste found in the pasar inpres Ruteng)